Effects of Toxin Binder Supplementation via Drinking Water on The Growth Performance of Broiler Chickens - Listya Purnamasari; Dixie GE Mendoza; Joseph P Olarve; Joseph F dela Cruz (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
A four-week feeding trial was conducted to determine the effect of liquid toxin binder supplementation on the production performance of broiler chickens. A total of 400 seven-day-old Cobb broiler chicks were randomly distributed to four treatments following a Complete Randomized Design (CRD). The treatment groups consisted of the control group, continuous liquid toxin binder supplementation, reduced feed toxin binder inclusion, continuous liquid toxin binder supplementation, and intermittent liquid toxin binder supplementation. Each treatment was replicated four times with 25 chicks per replicate. The feeding trial was conducted from the age of 8th to 35th days of age. The acidifier used was a blend of activated charcoal, selenium, vitamin E, probiotics, prebiotics, mannan oligosaccharides, and bacterial cell wall components. The results showed significant effects (P<0.05) on the broilers' body weight gain, average daily gain, and feed efficiency from 8 to 14 days of age. Income over feed, chick, and medication cost of broilers was increased with continuous supplementation of liquid toxin binder and reduced feed toxin binder. This study indicates that continuous supplementation of liquid toxin binder and reducing the feed toxin binder is economically more advantageous to use in broiler production.